Altered Trust Learning Mechanisms Among Female Adolescent Victims of Interpersonal Violence. Issue 1 (January 2018) - Lenow, Jennifer; Cisler, Joshua; Bush, Keith
Early-life interpersonal violence (IV) is a significant risk factor for a broad range of mental health disorders, increased rates of re-victimization, and psychosocial dysfunction. However, the cognitive mechanisms by which these risks are conferred are largely unknown. The current study attempted to address this empirical gap. Thirty-two adolescent girls, aged 12 to 16 (15 victims of IV), completed a social learning task. A computational learning model was fit to the behavioral data (ratings of trustworthiness during the learning task) to test for group differences in the cognitive mechanisms by which adolescent girls learn to differentially trust others. Specifically, we tested for differences in task performance and subject-level learning parameters: learning rate (the extent to which preferences are updated with new information) and preference stochasticity (the extent to which preferences seem random). Adolescent girls who were victims of IV demonstrated significantly worse performance than their control counterparts. Among IV victims, we observed a relationship between higher learning rates and greater preference stochasticity. Theoretical and clinical implications are discussed.